Another kind of evidence : studies on internalization, annihilation anxiety, and progressive symbolization in the psychoanalytic process /: studies on internalization, annihilation anxiety, and progressive symbolization in the psychoanalytic process. (2018) - Freedman, Norbert; Hurvich, Marvin; LCSW, Ward, Rhonda; Geller, Jesse D; Hoffenberg, Joan
No abstract available